Educational Content as a Marketing Tool in Increasing Consumer Engagement - Mendrofa, Kristiurman Jaya; Saputra, Devid; Hermaya, Gading Octorio; Dakhi, Paskalis; Anindya, Annisa (International Journal of Business, Law, and Education, 2026)
In the rapidly evolving and highly competitive landscape of modern marketing, educational content has emerged as a vital strategic tool to enhance consumer engagement and build trust in products and services. This study investigates the role of literacy-based marketing through educational content across various business sectors in Indonesia, including finance, technology, retail, and automotive. Employing a qualitative case study approach and content analysis of marketing campaigns, the research reveals that informative and relevant educational content significantly improves consumer understanding, encourages active interaction with brands, and supports more informed purchasing decisions. The financial and technology sectors demonstrate effective implementation of literacy strategies via digital media such as webinars, video tutorials, and online learning modules. In contrast, the retail and automotive sectors show room for growth in adopting educational marketing content. The findings underscore that literacy-driven marketing boosts brand awareness and consumer loyalty and fosters sustainable trust. The study recommends the development of creative, interactive, and personalized educational content tailored to local market characteristics to strengthen consumer engagement. This research contributes valuable insights for businesses that leverage literacy as a competitive advantage in Indonesia’s increasingly digital and complex market environment.